Experimental Evaluation of Energy Saving Task Scheduling (ESTS) in Cloud Computing - Kalyana Sundaram, N; S.P.Rajagopalan, Dr (International Journal of Engineering and Technology, 2018)
Cloud Computing provides services, on-demand access, infrastructure, storage of data and application. Â It possesses the reliability, availability and the scalability. One of the issues in cloud computing is Energy Saving. In this paper, the proposed work is Energy Saving Task Scheduling (ESTS) methodology. The aim of this methodology is to show the performance comparison of all the task scheduling types. Task scheduling or Job scheduling is referred to as policies that control the work order to be performed by a computer system. Types of Task Scheduling are Shortest Job First (SJF), First Come First Serve (FCFS), Round Robin (RR) and Priority Scheduling. In each type of schedule, the processes used by the parameters were calculated. Finally, the performance comparison is made in scheduling algorithms and shows better results. This method is implemented in net beans toolkit.Â Â